Plan de intervención para prevención de riesgos laborales en los trabajadores de la mina reina del cisne de la empresa Oroporto - Ordóñez Apolo, Kennia Del Carmen (2017)
Mine workers are in constant danger even when they do not wear appropriate protective clothing such as gloves, oxygen masks when entering deeper parts, the use of clothing and proper footwear, in addition to knowing that when exploding the rock must be away Since the silica that emanates silicosis is the same as a chronic degenerative disease of the respiratory tract, to this added the constant danger of falling, fractures blows, drowning. The design of the study was descriptive and non-experimental. The data collection was carried out by means of the application of a questionnaire and the same observation that was applied to 210 workers of the mine, with the obtained results a diagnostic base was created that was the starting point for the elaboration of the Plan of Intervention for the prevention of occupational hazards that is directed to the improvement of the signage in the company, also to the adequate storage, transport and manipulation of explosives, and to the control of gases dust and noise. Among the most relevant results are the main pathologies such as cough, flu (60%), the most frequent occupational hazards such as chemical, biological, mechanical and ergonomic 100%, and between 16% and 90% do not meet With biosafety standards.